Control over WirelessHART Network through a Host Application: A WirelessHART Network Control Proposal - Soto, Viyils Sangregorio; Muller, Ivan; Winter, Jean M.; Pereira, Carlos Eduardo; Netto, Joao C. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2014)
The number of wires needed for effecting control increases with the complexity of the automation. In the last years, this has limited the development of process automation in the industry. Wireless networks offer an evolution to these restrictions, bringing facilities in reconfiguration and portability to mobile terminals. Meanwhile, some paradigms as, for example, security, reliability and latency, make it difficult for new technologies to be inserted into the industrial area. One of the major difficulties in wirelessly networked control systems is that the delay induced by the network in the control loop may cause degradation of the control performance and can destabilize the plant. This research offers a general view of the WirelessHART protocol for networked control systems, including the necessary mechanisms for an effective control loop through a host application. It also shows that is possible to perform control over WirelessHART networks with the control module placed in a host application using an acceptable working sample period for a process plant in a networked control system.